KeepAble Cancer Community Centre® - Loh, S.Y. (University of Malaya, 2014)
Keepable cancer community project - a community project to provide supportive-rehabilitative care to cancer survivors in the community; and to raise awareness about cancer prevention or Cancer Control via healthy community Lifestyle. Lastly, bringing people together against cancer.